Digital Transformation and Circular Economy in Mine Tailings Management: A Multi-Country Review of Emerging Practices - Aridaman Walia; Martin Anda; Jonathan Whale; Om Dubey (Circular Economy and Sustainability, 2026)
Mine tailings present a growing global environmental and economic challenge requiring integrated technological, regulatory, and circular economy responses. This review examines international trends in tailings management, with particular focus on Western Australia, drawing on comparative evidence from Brazil, Chile, South Africa, Canada, and Finland. It analyses digital innovations (AI, IoT, blockchain, UAVs) alongside circular economy strategies, evaluates regulatory frameworks, and identifies key research gaps in economic assessment, long-term environmental monitoring, technological integration, and community engagement. Western Australia is identified as well-positioned to lead responsible tailings management, with lessons applicable across the global mining sector.